Enteric methane emission response to peanut (Arachis hypogaea) and cowpea (Vigna unguiculata) haulms supplementation in zebu cattle diets - Somda, Bienvenu D’Ela; Bastianelli, Denis; Gbenou, Gérard Xavier; Houngue, Wilfrid; Sib, Ollo; Dossa, Luc Hippolyte; Bonnal, Laurent; Bougouma-Yameogo, Marie Christiane Valérie; Assouma, Mohamed Habibou (Frontiers in Animal Science, 2025)
Improving the quality of ruminant rations is a promising strategy for mitigating the climate impact of livestock farming in West Africa. Legume crop coproducts such as peanut (Arachis hypogaea) and cowpea (Vigna unguiculata) haulms are a high-protein fodder commonly used by agropastoral farmers during the dry season. This study evaluated their potential to reduce enteric methane (eCH4) emissions when used as supplements for Panicum maximum C1 hay. Ten Sudanese Fulani zebu bulls (49 ± 1.2 months; 183.7 ± 15.9 kg) were housed individually and fed 11 diets ad libitum: a control diet of 100% P. maximum and 10 experimental diets combining P. maximum with either peanut or cowpea haulms at ratios of 85:15, 70:30, 55:45, 40:60, and 25:75. Each trial lasted 21 days, comprising a 14-day adaptation period and a 7-day data collection period for feed intake, digestibility, and eCH4 emissions. The latter were measured six times daily using the GreenFeed system. Supplementation increased protein content by 47.5% to 183.5% and ADL by 2.6% to 48.2% while reducing the content of crude fiber, NDF, and ADF. Feed intake increased by 17.8% to 49.1% (p < 0.05), and digestibility improved by 4.6% to 9.9% (p < 0.05). Peanut haulms reduced eCH4 yield by up to 6.1% (p < 0.05), while cowpea haulms achieved reductions of 3.7%–4.8% (p = 0.14). The most effective mitigation was achieved with 75% peanut or 45% cowpea haulms, confirming the potential of legume coproducts to enhance feed efficiency and reduce eCH4 emissions in West African cattle systems.